Pengaruh Dukungan Teman Sebaya terhadap Regulasi Diri Santri di Pesantren - Nanda Mustika Meilan; Herlina; Mukhlis (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
Self-regulation is a crucial skill for students living in Islamic boarding schools (pesantren), where daily life is characterized by intensive social interactions, strict routines, and high demands for independence. In such contexts, peer support becomes an important social factor that may influence students’ ability to regulate their thoughts, emotions, and behaviors. This study aims to examine the effect of peer support on students’ self-regulation in pesantren settings. This study employed a quantitative correlational design involving 252 male and female students from Islamic boarding schools in Gunung Pati District, Semarang, selected through proportional sampling. Data were collected using the Peer Support Questionnaire (PSQ) and the Self-Regulation Questionnaire (SRQ). Multiple linear regression analysis was conducted to examine the contribution of different dimensions of peer support to students’ self-regulation. The results showed that peer support had a significant effect on students’ self-regulation (R = 0.654; R² = 0.360; p < 0.01), indicating a moderate to strong effect size. Specifically, emotional support, companionship support, and validation significantly predicted students’ self-regulation, while informational support did not show a significant effect. These findings suggest that affective and relational aspects of peer support play a more important role than informational support in fostering self-regulation among students in pesantren.